Penentuan Akor Piano dengan Algoritma Short Time Fourier Transform - Theresia Angel Oktarina Pasaribu; Luh Gede Astuti (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
This research aims to develop a system that is able to identify the key of piano chords in a piece of music using the Short Time Fourier Transform (STFT) method, which is carried out based on frequency analysis of the basic notes that form the piano chord. STFT is used to analyze the audio signal of a piano chord and decompose its frequency spectrum over time. This method is implemented in the Google Colab environment with the Python programming language. The data used is the Piano Triads Wavset dataset which contains combinations of notes in a piano chord. The analysis process begins with data exploration to understand the patterns in the chords, then the system carries out analysis to determine the key to the chords. Test results show that this system has an accuracy of 54.83% in determining piano chords.